PERHITUNGAN INDIKATOR KINERJA RUMAH SAKIT MENGGUNAKAN DATA WAREHOUSE (Studi Kasus di Rumah Sakit Umum Sengkang Sulawesi Selatan) - , Andi Tenri Sumpala Mangkona ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of hospitalwill lead to health service industry,so that the health services must be the primary focus. Information is very important role because it is used in making strategic, technical and dynamic decisionsin the hospital. Medical and doctorâs data that related to the patients in the hospital were still processed manually, thus it takes a long timeto process the data to obtain the information of the hospital performance indicators. So it needs an applications that is capable to measure the performance of the Hospital and storing large amounts of data. Data Warehouse application designed with star schema model which is consisted of four fact tables facilitate the hospitaldirector, head ofMedical and HealthServices analyzing data using OLAP functions. The results indicate that the multidimensional data model enables easy analysis of the medical data of the patients, easy measurement of the indicators of the health service of the hospital, including ALOS, BOR, TOI, NDR and GDR by making use of OLAP function and contour cube component.